2006
DOI: 10.1007/s11096-006-9008-8
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems in general practice: results from a development project in Denmark

Abstract: The pharmacist was able to identify drug-related problems and other possible quality problems with regard to quality assurance of individual patient's drug treatment. The GPs accepted and implemented the pharmacist's recommendations. It was feasible to implement the services and to establish well-functioning co-operation between the pharmacist and the GPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 7 publications
2
19
1
Order By: Relevance
“…This aligns with the findings of other studies assessing pharmacist medication reviews undertaken in clinic settings. 19,35,37 The high rate of implementation of recommendations (73.5%) in this study is comparable to other studies, 19,35,36 and is higher than in most studies evaluating medication reviews conducted outside of clinic settings. 19,38 Increased rapport between pharmacists and GPs, opportunities for face-to-face communication and access to patient medical files enabling more targeted reports are potential reasons why implementation rates are higher with co-location of pharmacists within clinics.…”
Section: Discussionsupporting
confidence: 79%
“…This aligns with the findings of other studies assessing pharmacist medication reviews undertaken in clinic settings. 19,35,37 The high rate of implementation of recommendations (73.5%) in this study is comparable to other studies, 19,35,36 and is higher than in most studies evaluating medication reviews conducted outside of clinic settings. 19,38 Increased rapport between pharmacists and GPs, opportunities for face-to-face communication and access to patient medical files enabling more targeted reports are potential reasons why implementation rates are higher with co-location of pharmacists within clinics.…”
Section: Discussionsupporting
confidence: 79%
“…Pharmacists may identify and resolve drug-related problems and improve pharmacotherapy, according to some published papers [27][28][29][30]. Application of our strategy on NSAIDs dispensing has had a positive impact on reducing the number of patients at risk of NSAID-induced gastropathy.…”
Section: Discussionmentioning
confidence: 99%
“…A Dutch study involving patients aged 65 years or over on six or more medicines also found an average of four medication-related problems per patient [25]. Similarly, a Danish study involving 40 patients who were all taking four or more medicines, found an average of three medication-related problems per person [23] and Australian studies found an average of three to four medication-related problems per patient [22,26].…”
Section: Multimorbidity and Problems With Medicine Usementioning
confidence: 97%
“…A number of studies have shown that of those at high risk of medication misadventure, the majority will have a medicationrelated problem [18,[22][23][24][25]. A US study involving 159 patients aged 65 years or over and dispensed three or more medicines found a mean of four potential medication-related problems per patient, of which 40% were resolvable [24].…”
Section: Multimorbidity and Problems With Medicine Usementioning
confidence: 99%